Has COVID-19 changed how people think about the drivers of health? If so, does it matter? - Nelson, Christopher; Martin, Laurie T.; Yeung, Douglas; Bugliari, Delia (Frontiers in Health Services, 2022)
Background: Could COVID-19 pandemic prompt shifts in Americans’ basic views on health mindset and policy solutions to health crises? Methods: A sample of 1,637 individuals rated the extent to which items (e.g., the role of environmental vs. individual factors) “may affect people’s health and well-being,” both before (2018) and during the pandemic. In summer 2020 and fall 2021 they responded to questions about vaccination status and perceptions of COVID-19 related policies. We assessed changes in health mindset using repeated measures logistic regression, and used cross-sectional logistic regressions to assess whether variations in mindset explain COVID-19 related attitudes and behavior. Results: Between 2018 and 2021 respondents gave increasing weight to where people live and genetic factors and less weight to the role of individual health choices. Views on the importance of access to healthcare did not change appreciably. Those who reported that health care and place have a strong effect on health and well-being were significantly more likely to get vaccinated. Moreover, those who strongly believed that place is important were significantly less likely to agree that their local government went too far in restricting their freedom and that the local economy should have been left alone. Conclusions: Respondents were more likely in 2021 than in 2018 to recognize social determinants of health, and this is associated with a greater openness to pandemic-control measures. It remains to be seen, however, whether the changes in health mindset will persist over time and contribute to changes in policy and practice.